2012
DOI: 10.1177/0038040711431587
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Educational Effects of Mass Imprisonment in America

Abstract: In some American schools, about a fifth of the fathers have spent time in prison during their child's primary education. We examine how variation across schools in the aggregation and concentration of the mass imprisonment of fathers is associated with their own children's intergenerational educational outcomes and ''spills over'' into the attainments of other students. We assess the association of this interinstitutional and intergenerational ''prison through school pathway'' with downward and blocked educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
104
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 59 publications
0
104
1
1
Order By: Relevance
“…Likewise, the parental well-being can serve as an explanation. Bad parental health conditions (Roos et al 2013) or parental imprisonment (Hagan and Foster 2012) are severe social distortions that can lead to academic failure.…”
Section: What Determines Educational Successmentioning
confidence: 99%
“…Likewise, the parental well-being can serve as an explanation. Bad parental health conditions (Roos et al 2013) or parental imprisonment (Hagan and Foster 2012) are severe social distortions that can lead to academic failure.…”
Section: What Determines Educational Successmentioning
confidence: 99%
“…Fewer in number are the studies that have explored whether type of parental incarceration (i.e., paternal vs. maternal) has a differential impact on outcomes among children (Foster and Hagan 2013;Hagan and Foster 2012b;Lee, Fang, and Luo 2013;Nebbitt et al 2013;Tasca, Rodriguez, and Zatz 2011).…”
Section: Current Researchmentioning
confidence: 99%
“…As parental imprisonment has become common for U.S. children, researchers have started to test the association between parental incarceration and the health and well-being of infants, children, and adolescents. Research in this area has shown not only that paternal incarceration is a risk factor for poor health and well-being among U.S. infants (Wildeman 2012), children (Geller et al 2012;Haskins 2014;Turney 2014;Wildeman 2011, 2013;Wildeman 2010), and adolescents (Foster and Hagan 2007;Lee, Fang and Luo 2013;Roettger and Boardman 2012;), but also that maternal incarceration is a risk factor for poor child health and well-being across the life-course (Lee, Fang, and Luo 2013;Cho 2009;Hagan and Foster 2012;Huebner and Gustafson 2007;Turney and Wildeman 2015;Wildeman and Turney 2014). Similar associations exist in a host of developed democracies, including England (e.g., Murray and Farrington 2005), Norway (e.g., Murray, Janson and Farrington 2007), the Netherlands (e.g., Besemer et al 2011), and Denmark (e.g., .…”
Section: Introductionmentioning
confidence: 99%